A genome-wide CRISPR screen reveals how diatoms thrive in dynamic light - Jon Doenier; Dimitri Tolleter; Sarah Frail; Giovanni Finazzi; Adrien Burlacot; Ellen Yeh (Proceedings of the National Academy of Sciences, 2026)
Diatoms are a highly diverse algal group with outsized impact on global primary production and marine carbon sequestration. They are red lineage phototrophs of complex endosymbiotic origin and therefore evolutionarily divergent from plants and other green lineage phototrophs that typically serve as photosynthesis models. To accelerate the discovery of unique diatom biology, we developed a genome-wide CRISPR/Cas9 screen in the marine diatom, Phaeodactylum tricornutum. Dynamic light conditions are common in nutrient-rich, well-mixed marine environments in which diatoms thrive. The P. tricornutum mutant library was grown in different light regimes, including both high light and fluctuating light. We identified a broad set of genes required for survival specifically in dynamic light, including effectors of cyclic electron flow (CEF) and enzymes catalyzing posttranslational modifications of Calvin cycle enzymes. Among genes of unknown function identified, we demonstrated that the red lineage-exclusive gene STROBE1 is a CEF potentiator required for CEF-dependent generation of a trans-thylakoid proton gradient. STROBE1 and other genes identified in this screen reveal unexpected mechanisms underlying the adaptation of diatoms to dynamic light environments. This genome-wide genetic screen in P. tricornutum will accelerate the unbiased discovery of novel gene functions in these ecologically important organisms.